The global governance of trade in agriculture: the role of tariff and non-tariff measures illustrated with an example of agricultural exports from South Africa to the EU - Subow, Valentina (Department of Political Studies, 2014)
Due to its importance to food security and employment, the agricultural sector is a source of international conflict and inherently vulnerable to shocks and insecurities in the past and present. Accordingly, nation-states view respective domesticagricultural sectors as an exception, which meritsprotectionism and which needs protection from the rigors of free market forces and international competition withoutincurring heavy social, economic and political costs. For that matter, states traditionally impose protectionist measures to guard domestic agricultural sectors from external shocks. Paradoxically, the implementation of widespread protectionist measures has led to increasing volatilities in the supply and demand of agricultural commodities, e.g. by causing subsidized surplus stock (Friedmann 1982: 86). Against the backdrop of deep structural frictions and the implementation of pervasive protectionist measures, intergovernmental organizations aim to liberalize the global governance of trade in agriculture.